Experimental evidence on tax salience and tax incidence - Andrea Morone; Francesco Nemore; Simone Nuzzo (Kiel Institute for the World Economy (IfW), 2016)
While a basic theoretical principle in public economics assumes that individuals'behaviour is fully- optimizer with respect to the introduction of a tax, an increasing body of research is presenting evidence that agents decision-making is often affected by non-negligible cognitive biases , which could be responsible for lower market performance as well as for deviations from s tandard theoretical predictions. This paper extends the latter strand of research focusing on two trend topics in public economics: tax salience and tax incidence. While the former refers to the prominence of the tax, the latter places emphasis on the statutory vs. factual division of tax payments. Is market performance affected by the salience of the tax? Is the incidence of a tax independent of which side of the market it is levied on (Liability-Side-Equivalence-Principle, LES)? We address these questions through a laboratory experiment in which one unit of a fictitious good is traded through a double-auction market ins titution. Bas ed on a panel data analys is , our contribution shows that a non-salient tax reduces both the allocational and informational efficiency o f the market with respect to the instance in which the tax is salient. Moreover, we show that the LES does not hold in practice.
Keywords: 330; Tax incidence; Tax salience; Liability Side Equivalence; Choice behaviour; Laboratory